Central African Republic : Staff Report for the 2009 Article IV Consultation and Fifth Review Under the Arrangement Under the Poverty Reduction and Growth Facility, Requests for Waiver of Nonobservance and Modification of Performance Criteria, and Financing Assurances Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Central African Republic. (IMF Staff Country Reports; Country Report, 2010)
This 2009 Article IV Consultation highlights that the Central African Republic has recorded the modest economic growth since the end of the internal conflict in 2003, recovering from decades of decline in living standards. Real GDP grew by 2 1\2 percent a year on average during 2004-08. In 2008 and early 2009, a series of domestic and external shocks hit the economy, beginning with unstable power supply, followed by price rises in imported commodities, and later the global recession. Executive Directors have underscored the importance of further strengthening fiscal management.